Analysis of Speed and Acceleration of Two Mobiles in the Study of One-dimensional Movement - Silva, Jizreel Pereira da (Physics Education Research Journal, 2023)
The work discusses the analysis of the speed and acceleration of two mobiles in the study of one-dimensional movement as part of the study of kinematics, addressing in the classroom the experimental part, being projected on the board by the data show projector, where students individually, configure the system in order to observe the behavior of the blue and red furniture, comparing with the theoretical discussion also developed in the classroom. We address in an introductory way how the thinkers, philosophers, and scientists of the time of Mesopotamia and the Middle East dealt with the question of the movement of bodies and the mixture of what they believed about religion and mythology. The proposal of the operations in the simulator makes the students seek their questions and raise questions to colleagues and the teacher because, in addition to enriching the teaching-learning process, it motivates students for future proposals and consequently eases understanding of the functioning of physical theories. At the end of the simulation, we discuss the results, understanding what can change in the behavior of a mobile in front of the acceleration activation about the constant uniform movement.